Coping Styles, Aggression and Interpersonal Conflicts among Depressed and Non-Depressed People - Amber Nazir; Humaira Mohsin (Tabriz University of Medical Sciences, 2013)
Background: The present study compared people with depressive symp¬toms and people without depressive symptoms with reference to their coping styles, level of aggression and interpersonal conflicts.Methods: A purposive sample of 128 people (64 depressed and 64 normal controls) was selected from four different teaching hospitals of Lahore. Both the groups were matched on four demographic levels i.e. age, gender, education and monthly income. Symptom Checklist-R was used to screen out depressed and non-depressed people. The Brief COPE, the Aggres¬sion Questionnaire and the Bergen Social Relationship Scale were used to assess coping styles, aggression and interpersonal conflicts respectively. The Independent t-test was used to compare the groups. Binary logistic Regression was also carried out to predict the role of research variables in causing depression.Results: The results showed that level of aggression and interpersonal conflict was significantly more in people with depressive symptoms as compared to control group. On the other hand control group was using more adaptive coping styles than people with depressive symptoms but no difference was found in the use of maladaptive coping styles. Conclusion: The present findings revealed that coping styles, aggression and interpersonal conflicts play important role in depression. Therefore, these dimen-sions must be considered while dealing with the depressive patients. Implications for preventive work are also discussed in the light of previous researches.